CIRCULAR ECONOMY AND ITS IMPLICATIONS ON GREEN ECONOMIC GROWTH IN INDONESIA: UIN Sunan Ampel Surabaya - Nadira Amalia; Lathifah, Nurul (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This research discusses the implementation of circular economy in Indonesia and its impact on green growth. Indonesia, as a country with abundant natural resources, faces great challenges in waste management, thus the application of circular economy becomes relevant to create a more efficient and environmentally friendly economic system. The main focus of this research is to analyze how circular economy principles can be applied to support environmental sustainability and national economic growth. In addition, this research also evaluates the impact of the green economy on Indonesia's GDP growth, by examining how green economy policies can encourage innovation, create green jobs, and improve the competitiveness of the Indonesian economy in the global market. The method used is qualitative research with a literature study approach, which allows for an in-depth analysis of this topic. The results show that the implementation of a circular economy has great potential to boost the green economy in Indonesia.